Experimental study of the wake homogeneity evolution behind a horizontal axis tidal stream turbine. (June 2021) - Zhang, Zhi; Zhang, Yuquan; Zhang, Jisheng; Zheng, Yuan; Zang, Wei; Lin, Xiangfeng; Fernandez-Rodriguez, E.
Abstract: The influence of increased ambient turbulent intensity (ATI) on the wake of a three bladed tidal turbine has been measured experimentally in a recirculating water flume. The velocity deficit, turbulence intensity and Reynolds stress data of the wake was obtained from three-dimensional transient measurements, given via a detailed Acoustic Doppler Velocimeter. The disc-integrated velocity deficit and turbulence intensity were used to describe the performance of downstream turbine and wake homogeneity in a qualitative manner. Meanwhile, the principal values of Reynolds-stress anisotropy tensor and Lumley triangle were used to illustrate the degree of turbulence anisotropy within the turbine's wake. From results, the slightly increased ATI would accelerate the far wake recovery, decrease inhomogeneity and increase the energy utilization of downstream turbine and degree of wake turbulence anisotropy. The presented results are crucial in the view of investigation of the effect of ATI on wake propagation processes.